Superior mechanical properties of sulfonated graphene reinforced carbon-graphite composites. (July 2019) - Tu, Chuanjun; Hong, Lirui; Song, Tenghui; Li, Xuanke; Dou, Qinbao; Ding, Yichao; Liao, Tingting; Zhang, Sisi; Gao, Guoqiang; Wang, Ziqiu; Jiang, Yonghua
Abstract: The unavoidable defects in the structure of carbon-graphite composites, such as microcracks, have severe effects on their behaviors and performances in application. The introduction of graphene in carbon-graphite materials is considered as an effective strategy to regulate their structures and properties. Here, sulfonated graphene with abundant sulfonic acid groups was introduced into ultrafine petroleum coke powders, which could effectively prevent and reduce the generation of microcracks during preparation process of carbon-graphite composite. As a consequent, the prepared composites reinforced by doping 1 wt% of sulfonated graphene demonstrate obviously enhanced mechanical properties with flexural and compressive strength of 57.5 ± 3.8 MPa and 121.0 ± 2.3 MPa, respectively, which is 2.5 times higher than that of pure carbon-graphite counterparts. It indicates that the addition of sulfonated graphene as carbon reinforcement in carbon-graphite composites effectively improve interaction between tar pitch and coke powders, which increases the carbonized degree in roasting process, thus substantially polish up the structure integrity and the performance of carbon-graphite composites. Graphical abstract: Image 1